Penguatan Parenting Digital Bagi Orang Tua TK Islam Plus Baitussalam Kuningan - Yogi Iskandar; Ika Chandra Destiyanti; Nunung Nuryati; Anggi Pramowardhani; Iman; Setiana; Darmayanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2026)
The rapid development of digital technology has created new challenges for parents in raising early childhood children, particularly regarding gadget supervision, child protection from sexual violence, and the prevention of child grooming. Based on preliminary observations and needs assessment questionnaires conducted at TK Islam Plus Baitussalam Kuningan, most parents still experienced difficulties in implementing digital parenting and supervising children’s digital media use. This community service activity aimed to improve parents’ understanding of adaptive parenting and child protection in the digital era. The activity employed a Structured Training Approach consisting of socialization, material presentation, discussion, practical education sessions, and evaluation. The participants consisted of 35 parents of students from TK Islam Plus Baitussalam Kuningan. The evaluation used pre-test and post-test instruments along with participant response questionnaires. The results showed that the average participant score increased from 62.4 in the pre-test to 86.7 in the post-test. In addition, 85% of participants demonstrated improved understanding regarding authoritative parenting and child protection in the digital era, while 90% stated that the seminar materials were relevant to current parenting needs. This activity positively contributed to improving parents’ digital parenting literacy and encouraged wiser supervision of children's digital media use within the family environment.